Smartphone-Based Colorimetric Platform with RGB-CIELAB Multivariate Regression and 3D-Printed Illumination for Portable Multi-Analyte Detection - Manurung, Robeth Viktoria; Telaumbanua, Jonathan Edwards; Lim, Richard Anthony; Astuti, Winda; Mada, Dedi; Andreani, Agustina Sus (National Research and Innovation Agency, 2025)
Smartphone-based colorimetry has become a promising alternative to bulky and expensive spectrophotometers for portable and field analysis. This study aims to develop Colorizer, a modular smartphone-based colorimetric platform that provides accurate and affordable measurements for environmental, chemical, and biomedical applications. The system combines a custom Android app with a 3D-printed sampling station featuring controlled LED illumination, RGB-to-CIELAB conversion, calibration blanking, and multivariate regression modeling to ensure consistent measurements across devices. Illumination is controlled by an ESP32 microcontroller and activated via Bluetooth inside a light-tight chamber to minimize ambient interference. Validation experiments with synthetic dye assays showed strong agreement for red and yellow standards (R² = 0.944 and 0.940, RMSE = 6.503 and 6.955) and lower accuracy for blue assays (R² = 0.868, RMSE = 10.423), likely due to reduced signal-to-noise ratio at higher absorbance. These findings confirm that the platform delivers reliable and portable performance while functioning fully offline with locally stored calibration data. The study suggests that Colorizer offers a practical, low-cost alternative to benchtop spectrophotometers, with future work to validate its use with real-world analytes such as water contaminants, food safety markers, and clinical biomarkers.